Procedure of semantic-sense analysis of the research of the development of akme-oriented mature personality - Tkachenko, Oleksandr (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2019)
The development of a mature personality is considered in the context of its holistic and purposeful presentation in the form of a generalized category of the work of life and an acme-oriented mature personality, as an integrative-holistic entity. This education is systematically structured on the basis of the Axi-vector of higher values at the pre-reflexive, reflective and spiritual levels and the acme vector according to the stages of acme orientation. The article presents the procedure of the semantic-sense analysis of the research of the development of akme-oriented mature personality. The following experimental procedure for semantic-sense analysis of narratives is presented. 1) Semantic analysis, which allows to identify the "semantic field" (SF) and form a "concentration sense" (CS). 2) Correlation analysis, which makes it possible to single out the "common semantic core" (CSC), to determine the correlation coefficient, as well as the "coincidence" of identical words. 3) Sense analysis, which envisages the creation of a "common concentrated sense" (CCS) and a "specific concentrated sense" (SCS), which was used in the study of the development and formation of the model acme-oriented mature personality (AOMP). The article deals with the procedure of semantic-semantic analysis on the example of one of the most stressful situations (the first battle) of combat operations (DB) under counter-terrorism operation (ATO), when the focus is on axiological meanings. The proposed procedure for semantic-semantic analysis of narratives is an effective tool that consists of standardized techniques that are valid and reliable. Also, the complex application of these methods, and thanks to individual generalization with the help of a competent expert, can produce a qualitatively new result in the form of axiological meanings. This makes it possible to conduct an experimental procedure in combat and is, in turn, an effective tool for psychological research in crisis situations. Therefore, the results presented in the article are an achievement that is of practical importance, both for peer review and for the purpose of psychotherapy.